UV cavity enhanced absorption spectroscopy of the hydroxyl radical - Hancock, G; Kasyutich, V (2004)
We present the application of a continuous-wave ultra-violet tuneable light source for detection of the hydroxyl radical (OH) using cavity-enhanced absorption spectroscopy of the Q11(2) and Q21(2) absorption lines in the A2∑+(v′ = 0) ← X2Π3/2(v″ = 0) band at ca. 308 nm. A tuneable infra-red diode laser operating at 835 nm and either an Ar+ laser or a single frequency continuous-wave intracavity frequency-doubled diode laser, both operating at ca. 488 nm, were used to produce 0.1-0.5 μW of tuneable radiation at ca. 308 nm by sum frequency generation in a β-BaB 2O4 crystal. Cavity enhanced absorption spectroscopy was used to detect OH generated by UV photolysis of water vapour in argon, nitrogen, neon and helium at atmospheric pressure. A noise-equivalent (1σ) absorption sensitivity of 2.1 × 10-7 cm-1Hz -1/2 measured over 128 scans in a time of 1.16 s was demonstrated with mirrors of reflectivity 0.9963 in a cavity of length 58.5 cm for a ∼ 2 cm-1 scanning range at a UV power of ∼ 0.5 μW. An OH detection limit (1σ) of 3.84 × 109 molecule cm-3 was estimated in argon at atmospheric pressure. OH collisional broadening in humidified N2, Ar, Ne and He was determined at atmospheric pressure.